GAYA HIDUP DAN RISIKO KECELAKAAN PADA PENGEMUDI BUS ANTAR KOTA ANTAR PROVINSI (AKAP) - Pratiwi Kusuma Putri; Kawi Kawi; Ratna Muliawati; Baju Widjasena (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2019)
Land traffic accident incidents tend to increase. One of the contributors to land traffic accidents is the Inter-City Inter-Province bus accident (AKAP). This AKAP bus accident risks causing losses because it involves the safety of passengers and other road users. This accident risk is closely related to the health and fitness of the bus driver. This study aims to determine the relationship between lifestyle and risk of accidents on AKAP bus drivers who cross the Kendal Regency. This study is an analytical-analytical study. The research was conducted at RM.X with 40 respondents as AKAP bus drivers. Data collection through interviews with questionnaires. Data were analyzed statistically by the chi square test. The results showed no significant relationship between exercise habits (p value = 0.654), rest pattern (0.279), and diet with the incidence of workplace accidents in AKAP Bus drivers. All AKAP bus drivers (100%) have an unbalanced diet. AKAP bus drivers are advised to pay more attention to fitness, rest habits and eating habits, so that when driving is always in top condition.